Leader-managers in the public sector managing for results - Dukakis, Michael S (Michael Stanley) 1933-; Portz, John 1953- (M.E. Sharpe, 2010)
At a time of doubt and concern about government and its capacity to serve the public, this book highlights the critical skills and practices that characterize good leadership and good management